Satisfaction and utilization patterns of social security allowance among senior citizen in Bharatpur ward no-6, Nepal - Poudel, Eak Narayan; Khanal, Gayatri; Koirala, Subash (Journal of Chitwan Medical College, 2022)
Background: The quality of the senior citizens has become a public health concern. The Quality of the life of senior citizen is affected by many factors. Among them one of the strong factors is social security allowance. Misuse on social security allowance and dissatisfaction is increasingly recognized among senior citizens hence, the present study aimed to explore satisfaction with and utilization of the old age allowance among older people. Methods: The Community based cross-sectional study using face to face interview was carried out among senior citizen in Bharatpur Metropolitan ward no -6. Asystematic Random sampling method was used. We used IBM Statistical software version 20 to carry descriptive and bivariate analysis. Results: Around 134(77.4%) respondent mentioned that, they were capable to spend their Social Security Allowance themselves. Senior citizen was satisfied with the social security allowance given by government while 38.7% were unsatisfied. Satisfaction status of social security allowance significantly associated with living condition [with familymembers (COR=3.18; CI=1.54-6.57)], occupation[other than farm (COR=2.18; CI=1.16-4.09)] Conclusions: The Social security Allowance for senior citizen is a necessary and proper utilization can give important contribution to older people connected with family and community.